2017
DOI: 10.1038/s41598-017-08684-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of radiotracers targeting the melanin-concentrating hormone receptor 1: [11C]SNAP-7941 and [18F]FE@SNAP reveal specific uptake in the ventricular system

Abstract: The MCHR1 is involved in the regulation of energy homeostasis and changes of the expression are linked to a variety of associated diseases, such as diabetes and adiposity. The study aimed at the in vitro and in vivo evaluation of [11C]SNAP-7941 and [18F]FE@SNAP as potential PET-tracers for the MCHR1. Competitive binding studies with non-radioactive derivatives and small-animal PET/CT and MRI brain studies were performed under baseline conditions and tracer displacement with the unlabelled MCHR1 antagonist (±)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…4c). This finding is supported by previously conducted experiments [25] and is likely a result of the high unspecific binding and metabolic degradation of [ 18 F]FE@SNAP. Furthermore, a drop in the TAC of both radiotracers after displacement with 15 mg/kg (±)-SNAP-7941 could be detected for the lung (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…4c). This finding is supported by previously conducted experiments [25] and is likely a result of the high unspecific binding and metabolic degradation of [ 18 F]FE@SNAP. Furthermore, a drop in the TAC of both radiotracers after displacement with 15 mg/kg (±)-SNAP-7941 could be detected for the lung (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In this context, it has to be highlighted that experiments on living cells, as performed in the present study, enhance the understanding of the complex interplay between the radiotracer and the dedicated biological target [ 39 ]. Moreover, previous experiments revealed higher binding affinity for (±)-SNAP-7941 ( K i = 3.91 ± 0.74 nM) compared to FE@SNAP ( K i = 9.98 ± 1.12 nM) [ 25 ]. Based on current and previous results, [ 11 C]SNAP-7941 exhibits an improved target affinity and superior selectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These successful integrations show that a set of knowledge, skills and competencies can be perfectly transferred from the clinic into preclinical imaging to improve and evaluate experimental procedures. Some evidence has also shown that an experienced NMT or radiographer in this sector can take on roles as research investigators (Zeilinger et al 2017;Dillenseger et al 2019). Involvement of NMTs and radiographers in new preclinical molecular and quantitative imaging methods, which are vastly growing fields, could be highly beneficial for their own professional development as a winwin complementary bridge with the clinical field (Dillenseger et al 2019), but also could be an enabler for more fundamental works.…”
Section: Resultsmentioning
confidence: 99%
“…-Methodological developments -Evaluations (new procedures, pharmaceutical agents or devices) -Workflow organisation There are many examples of studies carried out by NMTs and radiographers. For instance, one revealed specific absorption of a number of radiotracers in the ventricular system in rats (Zeilinger et al 2017). Another one focuses on gadolinated agents' injection pathways in preclinical MRI, taking into consideration the animal welfare and showing that subcutaneous routes could be an alternative to intravenous routes (Dillenseger et al 2019).…”
Section: Multimodal Preclinical Imaging Lab: An Opportunity For Nmt Amentioning
confidence: 99%